Spatial organization of restaurant industry in Kharkiv region - Kobylin, P. (ХНУ ім. В. Н. Каразіна, 2012)
The article defines the term «restaurant industry», its place in economic development, have been analyzed the dynamics of trade turnover of restaurant industry companies, their number and the factors affecting on the distribution of restaurants’ network by districts of Kharkiv region have been found out.
В статье определено понятие «ресторанное хозяйство», его место в развитии хозяйства, проанализирована динамика развития товарооборота предприятий общественного питания, их численности и выяснены факторы, влияющие на распределение сети ресторанного хозяйства по районам Харьковской области.
Keywords: cafe; cafeteria; catering; public catering; restaurant industry; trade turnover of restaurant industry enterprises